Experimental and Modeling Investigations of Miniaturization in InGaN/GaN Light-Emitting Diodes and Performance Enhancement by Micro-Wall Architecture - Zhang, Yiping; Lu, Shunpeng; Qiu, Ying; Wu, Jing; Zhang, Menglong; Luo, Dongxiang (Frontiers in Chemistry, 2021)
The recent technological trends towards miniaturization in lighting and display devices are accelerating the requirement for high-performance and small-scale GaN-based light-emitting diodes (LEDs). In this work, the effect of mesa size-reduction in the InGaN/GaN LEDs is systematically investigated in two lateral dimensions (x- and y-directions: parallel to and perpendicular to the line where p-n directions are) both experimentally and numerically. The role of the lateral size-reduction in the x- and y-directions in improving LED performance is separately identified through experimental and modeling investigations. The narrowed dimension in the x-direction is found to cause and dominate the alleviated current crowding phenomenon, while the size-reduction in the y-direction has a minor influence on that. The size-reduction in the y-orientation induces an increased ratio of perimeter-to-area in miniaturized LED devices, which leads to improved thermal dissipation and light extraction through the sidewalls. The grown and fabricated LED devices with varied dimensions further support this explanation. Then the effect of size-reduction on the LED performance is summarized. Moreover, three-micro-walls LED architecture is proposed and demonstrated to further promote light extraction and reduce the generation of the Joule heat. The findings in this work provide instructive guidelines and insights on device miniaturization, especially for micro-LED devices.